Defensive tactics against takeovers in theory and practice in the USA, the UK, South Africa, Germany and the EU - Kley, Christian (Global Risk Governance Programme, 2026)
After the takeover wave of the 1970s and 1980s in the USA and in the United Kingdom the 1990s have experienced a more moderate takeover market. Nonetheless takeovers nowadays are a major issue all over the industrialised world, in economic and legal circles as well as in society. One rather eccentric American author has even compared the takeover issue with the national debt, defence spending, and prayer in public schools. Regarding the huge amounts of money involved in takeover battles one might easily be inclined to such extreme statements.